Synthesis and Profiling of a Novel Potent Selective Inhibitor of CHK1 Kinase Possessing Unusual N-trifluoromethylpyrazole Pharmacophore Resistant to Metabolic N-dealkylation - Samadder, Pounami; Suchánková, Tereza; Hylse, Ondřej; Khirsariya, Prashant; Nikulenkov, Fedor; Drápela, Stanislav; Straková, Nicol; Vaňhara, Petr; Vašíčková, Kateřina; Kolářová, Hana; Binó, Lucia; Bittová, Miroslava; et al. (Molecular cancer therapeutics, 2017)
Checkpoint-mediated dependency of tumor cells can be deployed to selectively kill them without substantial toxicity to normal cells. Specifically, loss of CHK1, a serine threonine kinase involved in the surveillance of the G2-M checkpoint in the presence of replication stress inflicted by DNA-damaging drugs, has been reported to dramatically influence the viability of tumor cells. CHK1's pivotal role in maintaining genomic stability offers attractive opportunity for increasing the selectivity, effectivity, and reduced toxicity of chemotherapy. Some recently identified CHK1 inhibitors entered clinical trials in combination with DNA antimetabolites. Herein, we report synthesis and profiling of MU380, a nontrivial analogue of clinically profiled compound SCH900776 possessing the highly unusual N-trifluoromethylpyrazole motif, which was envisioned not to undergo metabolic oxidative dealkylation and thereby provide greater robustness to the compound. MU380 is a selective and potent inhibitor of CHK1 which sensitizes a variety of tumor cell lines to hydroxyurea or gemcitabine up to 10 times. MU380 shows extended inhibitory effects in cells, and unlike SCH900776, does not undergo in vivo N-dealkylation to the significantly less selective metabolite. Compared with SCH900776, MU380 in combination with GEM causes higher accumulation of DNA damage in tumor cells and subsequent enhanced cell death, and is more efficacious in the A2780 xenograft mouse model. Overall, MU380 represents a novel state-of-the-art CHK1 inhibitor with high potency, selectivity, and improved metabolic robustness to oxidative N-dealkylation. Mol Cancer Ther; 16(9); 1831-42. ©2017 AACR.
Keywords: modely nemocí na zvířatech; metylace; Humans; Dealkylation; dealkylace; Cell Cycle; nádorové buněčné linie; Antineoplastic Agents; Mice; zvířata; Molecular Structure; chemorezistence; Disease Models, Animal; Pyrimidines; protinádorové látky; xenogenní modely - testy protinádorové aktivity; apoptóza; Protein Kinase Inhibitors; checkpoint kinasa 1; Cell Cycle Checkpoints; inhibitory proteinkinas; pyrimidiny; Drug Resistance, Neoplasm; biologické markery; kontrolní body buněčného cyklu; myši; Dose-Response Relationship, Drug; Animals; vztah mezi dávkou a účinkem léčiva; lidé; Checkpoint Kinase 1; Pyrazoles; Biomarkers; buněčný cyklus; Xenograft Model Antitumor Assays; Cell Line, Tumor; pyrazoly; Apoptosis; molekulární struktura; Methylation